(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This systematic review aims to describe the clinical and paraclinical characteristics and analyze the treatment outcomes of endometrial cancer in recent years. Method: A narrative review. Results: The disease predominantly occurs in the age group of 56-58 years and is closely associated with metabolic syndrome (obesity, diabetes, and hypertension). Abnormal uterine bleeding is the most prevalent symptom, occurring in 90-95.5% of cases. On transvaginal ultrasound, an endometrial thickness of ≥ 15.8 mm and a color Doppler score ≥ 2 according to the IETA criteria are strong predictors of malignancy. Surgery (preferably laparoscopic) combined with adjuvant chemoradiotherapy remains the cornerstone of treatment. The 5-year overall survival rate in Vietnam has reached approximately 80%, which is comparable to major international clinical trials such as PORTEC-3 and NSGO/EORTC. Conclusion: Abnormal uterine bleeding and IETA-standardized Doppler ultrasound are highly valuable for screening and early diagnosis. Individualizing multimodality treatment protocols based on risk stratification significantly improves patient survival outcomes.